2014
DOI: 10.1016/j.bmcl.2014.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization of (±) dihydrotetrabenazine for copper-64 labeling towards long-lived radiotracers for PET imaging of the vesicular monoamine transporter 2

Abstract: Dihydrotetrabenazine (DTBZ) derivatized from (+) Tetrabenazine (TBZ) has been used for imaging the expression of VMAT2 when labeled with 11C (t1/2 = 20.3 min.) or 18F (t1/2 = 110 min.) in neurodegenerative diseases or pancreatic beta-cell. Because 11C or 18F radiolabels are only available in the proximity of a biomedical cyclotron facility, here we report our work of derivatizing (+) and (−) DTBZ using a 64Cu-specific bifunctional chelator scaffold (64Cu: t1/2 = 12.7 h) for the preparation of long-lived VMAT2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Currently, there have only been limited reports using other PET nuclides. Recently, Kumar et al[ 44 ] reported synthesis of the 64 Cu-specific bifunctional chelator scaffold DTBZ analogues: 64 Cu-CB-TE2A-(+)-DTBZ (IC 50 = 16.8 ± 6.9 nmol/L) and 64 Cu-CB-TE2A-(-)-DTBZ (IC 50 = 253.2 ± 107.8 nmol/L). As we knew that, the IC 50 values of (+)-DTBZ and (-)-DTBZ were 0.97 ± 0.48 nmol/L and 2.2 ± 0.3 μmol/L, respectively[ 45 ].…”
Section: C- 18 F- and 64 mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there have only been limited reports using other PET nuclides. Recently, Kumar et al[ 44 ] reported synthesis of the 64 Cu-specific bifunctional chelator scaffold DTBZ analogues: 64 Cu-CB-TE2A-(+)-DTBZ (IC 50 = 16.8 ± 6.9 nmol/L) and 64 Cu-CB-TE2A-(-)-DTBZ (IC 50 = 253.2 ± 107.8 nmol/L). As we knew that, the IC 50 values of (+)-DTBZ and (-)-DTBZ were 0.97 ± 0.48 nmol/L and 2.2 ± 0.3 μmol/L, respectively[ 45 ].…”
Section: C- 18 F- and 64 mentioning
confidence: 99%
“…As we knew that, the IC 50 values of (+)-DTBZ and (-)-DTBZ were 0.97 ± 0.48 nmol/L and 2.2 ± 0.3 μmol/L, respectively[ 45 ]. The VMAT2 specific binding affinity of 64 Cu-CB-TE2A-(+)-DTBZ was not compromised by their chemical modifications, while that of its (-) counterpart remained low as in 11 C- or 18 F-labeled (±) DTBZ[ 44 ]. Currently, there are no further reports on PET imaging using 64 Cu-CB-TE2A-(+)-DTBZ in animal studies.…”
Section: C- 18 F- and 64 mentioning
confidence: 99%
“…The value of these compounds extends beyond the treatment of hyperkinetic disorders. The high VMAT2 affinity of (+)-(2 R ,3 R ,11b R )-DTBZ ( K i 0.97 nM) has spurred the development of radiolabeled analogues that are valuable imaging agents for diagnosing neurological conditions. Furthermore, Parkinsonian tremors can be modeled by dosing rodents with TBZ to induce tremulous jaw movements …”
mentioning
confidence: 99%